Support Teachers in the Education of Students with Autism and Asperger Syndrome in Integrated and Mainstream Schools - Szafrańska, Anida (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Anida Szafrańska, Support Teachers in the Education of Students with Autism and Asperger Syndrome in Integrated and Mainstream Schools. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 59–80. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.03 The article presents a pilot study of the tasks of support teachers in relation to students with autism, including those with Asperger’s syndrome. Data contained in the Educational Information System shows a significant increase in the number of students with this type of disorder studying in integrated units and mainstream schools. The education of students with autism and Asperger’s syndrome is difficult due to their deficits in the cognitive sphere, as well as problems in social and emotional functioning. When carried out in an appropriate manner, with relevant professional support, the inclusion of autistic children may be beneficial both for the children’s intellectual, social and emotional development, as well as other students.